Monitoring and Evaluation for Improving Academic Services and Teacher Performance - Surbakti, Muliana Br.; Purba, Arista (Indonesian Journal Education, 2024)
Efforts to achieve the goals of the program implemented in an organization must always be made by the management of the organization. Efforts to prepare a strategic plan are a commitment from the organization to realize the strategic plan . that monitoring has objectives, namely: (1) conformity or compliance according to predetermined standards and procedures, (2) inspection to determine sources of services to target groups, (3) accounting to determine social changes and economics that occur after the implementation of a number of public policies from time to time, (4) the explanation of the results of public policy is different from the objectives of public policy. The importance of monitoring and evaluation for the Learning Technology Study Program that in management evaluation isbcrucial stage in preparationbdevelopment program. Thereforebhow to carry out an evaluation comprehensive, structured and systematic must be understood correctly, so the resultscan be used as a basis for the process planning to achieve that goal the desired form of quality improvement sustainable.